Designing Phonetic Alphabet for Bahasa Indonesia (PABI) for the teaching of intelligible English pronunciation in Indonesia - Karlina, Yeni; Rahman, Amin; Chowdhury, Raqib (Indonesian Journal of Applied Linguistics, 2020)
The sociolinguistic development of English has placed a greater emphasis on intelligibility as the ultimate goal of pronunciation instruction. However, various studies have indicated that English pronunciation of Indonesian English learners was not satisfactory due to difficulties in learning English pronunciation and lack of emphasis given to the teaching of English pronunciation in English classrooms in Indonesia. In this paper we propose the development of Phonetic Alphabets for Bahasa Indonesia (PABI). This practical instrument allows English teachers and students in Indonesia to transcribe the pronunciations of English words into phonetic transcription with locally-appropriate readability and accessibility without compromising the pronunciation intelligibility. The development of PABI started with contrastive analysis of common phonemes in the two languages, i.e., English and Bahasa Indonesia (BI). Next, we identified the English phonemes missing in Bahasa Indonesia which English learners in Indonesia have to conceptualise. We then located those English sound ‘pairs’ which seem identical to Indonesians and are thus used interchangeably in BI. A corpus of 30,000 commonly used English words was transcribed in PABI using a computer software IPA to L1PA developed by Rahman and Bhattacharya (2020). Proposals to modify the IPA to suit the BI sound system entailed the adjustments in the consonant phonemes, vowel phonemes, and cluster sounds. These adjustments are expected to improve the readability and accessibility of the conventional IPA in facilitating the teaching and learning of intelligible English pronunciation in Indonesia. Practical uses of the PABI guidelines are drawn to improve its utility. Implications for the development of context sensitive and locally-appropriate pronunciation teaching and learning are drawn based on the findings.